Harnessing fungal bio-electricity: a promising path to a cleaner environment - Umar, Aisha; Mubeen, Mustansar; Ali, Iftikhar; Iftikhar, Yasir; Sohail, Muhammad Aamir; Sajid, Ashara; Kumar, Ajay; Solanki, Manoj Kumar; Kumar Divvela, Praveen; Zhou, Lei (Frontiers in Microbiology, 2024)
Integrating fungi into fuel cell systems presents a promising opportunity to address environmental pollution while simultaneously generating energy. This review explores the innovative concept of constructing wetlands as fuel cells for pollutant degradation, offering a practical and eco-friendly solution to pollution challenges. Fungi possess unique capabilities in producing power, fuel, and electricity through metabolic processes, drawing significant interest for applications in remediation and degradation. Limited data exist on fungi's ability to generate electricity during catalytic reactions involving various enzymes, especially while remediating pollutants. Certain species, such as Trametes versicolor, Ganoderma lucidum, Galactomyces reessii, Aspergillus spp., Kluyveromyce smarxianus, Hansenula anomala, have been reported to generate electricity 1200 mW/m 3 , 207 mW/m 2 , 1163 mW/m 3 , 438 mW/m 3 , 850,000 mW/m 3 , 2900 mW/m 3 , respectively. Despite the ecofriendly potential compared to conventional methods, fungi's role remains largely unexplored. The review delves into fungi's exceptional potential as fuel cell catalysts, serving as anodic or cathodic agents to mitigate land, air, and water pollutants while simultaneously producing the fuel and power. Applications cover a wide range of tasks, and the innovative concept of wetlands designed as fuel cells for pollutant degradationis discussed. Cost-effectiveness may vary depending on specific contexts and applications. Fungal fuel cells (FFCs) offer a versatile and innovative solution to global challenges, addressing the increasing demand for alternative bioenergy production amid population growth and expanding industrial activities. The mechanistic approach of fungal enzymes via microbial combinations and electrochemical fungal systems, facilitates the oxidation of organic substrates, oxygen reduction, and ion exchange membrane orchestration of essential reactions. Fungal laccase plays a crucial role in pollutant removal and monitoring environmental contaminants. Fungal consortiums show remarkable potential in fine-tuning FFC performance, impacting both power generation and pollutant degradation. Beyond energy generation, fungal cells effectively remove pollutants. Overall, FFCs present a promising avenue to address energy needs and mitigate pollutants simultaneously.